2019
DOI: 10.1007/s13770-019-00184-0
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Nanocomposite Scaffolds (Collagen/β-TCP/SrO) for Bone Tissue Engineering

Abstract: BACKGROUND: Nowadays, production of nanocomposite scaffolds based on natural biopolymer, bioceramic, and metal ions is a growing field of research due to the potential for bone tissue engineering applications. METHODS: In this study, a nanocomposite scaffold for bone tissue engineering was successfully prepared using collagen (COL), beta-tricalcium phosphate (b-TCP) and strontium oxide (SrO). A composition of b-TCP (4.9 g) was prepared by doping with SrO (0.05 g). Biocompatible porous nanocomposite scaffolds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…In the present study, the reduction in the degradation rate of nanocomposite scaffolds was probably due to the strong interaction between the hydroxyl groups of BN nanoparticles and the collagen amine groups during the crosslinking process. This behavior has been reported similarly in other studies 89–91 . For example, Aktourk et al 90 found that the presence of gold nanoparticles along with the cross‐linking process significantly reduced the degradation rate of collagen from about 100% to 20%.…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…In the present study, the reduction in the degradation rate of nanocomposite scaffolds was probably due to the strong interaction between the hydroxyl groups of BN nanoparticles and the collagen amine groups during the crosslinking process. This behavior has been reported similarly in other studies 89–91 . For example, Aktourk et al 90 found that the presence of gold nanoparticles along with the cross‐linking process significantly reduced the degradation rate of collagen from about 100% to 20%.…”
Section: Resultssupporting
confidence: 84%
“…For example, Aktourk et al 90 found that the presence of gold nanoparticles along with the cross‐linking process significantly reduced the degradation rate of collagen from about 100% to 20%. In addition, in another study, Goodarzi et al 91 showed that the addition of beta‐tricalcium phosphate and strontium nanoparticles to the collagen structure decreased the degradation rate and acidic products of collagen degradation. These results showed that the synthesized nanocomposite scaffolds have appropriate degradation rate and can be used to repair various tissues.…”
Section: Resultsmentioning
confidence: 98%
“…As well, research using NPs has been carried out in all areas of bio‐ and medical fields, 44,45 especially on the proliferation and differentiation of cells and wound healing using magnetic NPs 30 . Choi et al reported that 40 nm of chitosan‐conjugated gold NPs increased ALP, BSP, and OCN expression and enhanced the osteogenic differentiation of human adipose‐derived mesenchymal stem cells through Wnt/β‐catenin activation 46 .…”
Section: Discussionmentioning
confidence: 99%
“…In the regenerative and tissue engineering field, bio-mimicking scaffolds are routinely used to provide mechanical support for cell growth and tissue repair [103,104]. Biomaterials are derived from both natural materials and synthetic polymers with biocompatible properties [105].…”
Section: Matrix-based Platformmentioning
confidence: 99%